Comparative Efficacy of Nalbuphine Hydrochloride vs. Tramadol Hydrochloride for Post-Operative Analgesia in Orthopaedic Surgeries: A Double-Blind Randomized Control Study - Jahan, B Ishrat; Palakurthi, Nikhileshwar; Alugolu, Mrunalini; Ahmed Md, Khaliq (Journal of Neonatal Surgery, 2025)
Background: Effective postoperative analgesia is crucial for early mobilization and recovery in orthopaedic surgeries. This study compares the efficacy and safety of Nalbuphine Hydrochloride and Tramadol Hydrochloride for postoperative pain management in patients undergoing orthopaedic procedures. Methods: A double-blind, randomized controlled trial was conducted involving 100 patients who underwent various orthopaedic surgeries. Patients were randomly assigned to receive either Nalbuphine Hydrochloride or Tramadol Hydrochloride postoperatively. The primary outcomes measured were pain intensity using the Visual Analogue Scale (VAS) at specific time intervals and adverse effects. Secondary outcomes included hemodynamic stability and the need for additional analgesic doses. Results: Patients receiving Nalbuphine reported significantly lower VAS scores at 30 minutes (1.80 ± 0.50) and 540 minutes (2.00 ± 0.29) post-operation compared to those receiving Tramadol (2.21 ± 0.41 and 2.38 ± 0.58, respectively; p<0.01). Nalbuphine also demonstrated fewer adverse effects such as nausea and vomiting. Hemodynamic parameters were stable and comparable between the two groups. Conclusion: Nalbuphine Hydrochloride provides superior analgesia with fewer adverse effects compared to Tramadol Hydrochloride in the postoperative management of orthopaedic patients, making it a potentially preferable option for pain control in this population.